2023
DOI: 10.1172/jci169200
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic subunit of DNA-PK regulates transcription and splicing of AR in advanced prostate cancer

Beth Adamson,
Nicholas Brittain,
Laura Walker
et al.

Abstract: The ICR has a commercial interest in abiraterone, PARP inhibition in DNA repair-defective cancers, and PI3K/ AKT pathway inhibitors (with no financial interest). JSDB was named as an inventor, with no financial interest for patent 8,822,438 (Methods and Compositions for Treating Cancer), submitted by Janssen, which covers the use of abiraterone acetate with corticosteroids. He has been the chief investigator/principal investigator of many industry-sponsored clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, both our group and Adamson et al. 203 showed that DNA‐PKcs can regulate the RNA alternative splicing. 204 Aberrant androgen receptor (AR) signaling has proved to be the driver for prostate cancer (PC).…”
Section: Dna‐pkcs and Human Diseasesmentioning
confidence: 77%
“…Interestingly, both our group and Adamson et al. 203 showed that DNA‐PKcs can regulate the RNA alternative splicing. 204 Aberrant androgen receptor (AR) signaling has proved to be the driver for prostate cancer (PC).…”
Section: Dna‐pkcs and Human Diseasesmentioning
confidence: 77%
“…FMR1 has been previously identified as a promoter of PCa progression via the m6A-mediated circRBM33-FMR1 complex and has also been found to be correlated with a poor prognosis in the disease-free survival of PCa patients [47]. RBMX is known to control AR transcript metabolism by monitoring the turnover, synthesis, and splicing of AR variants and has been found to be correlated with a high Gleason score in PCa patients [48]. In contrast to the above findings, our results indicated that higher expression of HNRNPC, FMR1, and RBMX may have a protective effect aiding the survival of mCRPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-PK inhibition proved useful in re-sensitizing DU-145DxR PC cells to taxanes [137] and has been tested in combination therapy for mCRPC in a clinical trial (NCT02833883). However, given the additional role of DNA-PK in facilitating AR-mediated transcription [136,138], the prognostic and therapeutic value of DNA-PK in AR-independent PC remains uncertain.…”
Section: Dna Damage Repair (Ddr) Pathwaymentioning
confidence: 99%